The Importance of Hyperthyroid Screening in Acute Decompensated Heart Failure with Persistent Tachycardia Despite Optimal Decongestion: A Case Report - Wijayanto, Matthew Aldo; Myrtha, Risalina; Prabowo, Nurhasan Agung (The Indonesian Heart Association, 2022)
Background: Hyperthyroid has various effects on the cardiovascular system. Cardiac arrhythmias ranging from sinus tachycardia to atrial fibrillation and low/high cardiac output state to congestive heart failure are observed in patients with hyperthyroidism. If hyperthyroidism is recognized and treated early, the cardiac dysfunction could be corrected. This case presentation will discuss the importance of thyroid function screening. Case Illustration and Discussion: A man was admitted to the emergency department with signs and symptoms of acute decompensated heart failure. Further examination was performed to confirm the diagnosis, namely ECG, laboratory examination including thyroid function test, and echocardiography. During hospitalization, heart failure medication was given and up titrated. The patient was still tachycardia until hyperthyroid was corrected with anti-thyroid medicines. Conclusion: Hyperthyroidism can cause or worsen left ventricular dysfunction, especially in individuals with a history of cardiovascular disease. Thus, thyroid function tests should be assessed during initial laboratory examination, especially on patients with acute decompensated heart failure.This article has a related Erratum.